Effect of focused birth preparedness and complication readiness counseling on pregnancy outcome among females attending tertiary care hospital in Barabanki district, Uttar Pradesh, India - Mukesh Shukla; Nahid Zia Khan; Anjana Agarwal; Akhilesh Dutta Dwivedi; Jai Vir Singh; Shahnoor Alam (Wolters Kluwer Medknow Publications, 2019)
CONTEXT: Measures related to birth preparedness and complication readiness (BPCR) during pregnancy play an important role in producing better pregnancy outcome. If the pregnant females are properly counseled during antenatal visits, it could help in bringing out desirable behavior changes. AIMS: This study aims to study BPCR-related awareness and practices among the pregnant females and the effect of focused and structured birth preparedness counseling on complication readiness among pregnant females. SUBJECT AND METHODS: A facility-based follow-up study was conducted from July to December 2016, and a total of 130 pregnant females were enrolled. All study participants were initially assessed for various domains of BPCR index consisting of seven key indicators. The index reassessment was done again, after 1 month, during follow-up visit. Information regarding any pregnancy-related complication in due course and behavior was also recorded during successive follow-up. STATISTICAL ANALYSIS USED: The difference in pre- and postcounseling mean BPCR index was assessed using paired t-test, and McNemar's test was used for paired categorical data analysis. P < 0.05 was considered to be statistically significant. RESULTS: The postcounseling BPCR index (70.65 ± 19.18) was found to be significantly much higher as compared to pre-counseling baseline BPCR index (41.12 ± 11.34). Knowledge about danger signs of pregnancy, transportation services provided by government, financial assistance provided in Government schemes, identification of skilled birth attendant, mode of transportation, and arrangement of emergency blood donor was found to increase significantly after counseling. Abortion was found to occur significantly higher (about thrice) among those who had postcounseling BPCR index below average, i.e., <50% (P < 0.05). CONCLUSIONS: The results of the present study revealed that focused birth preparedness counseling on complication readiness could play an important role in increasing the baseline knowledge of pregnant females regarding pregnancy-related complications and bring out desirable ideal health-seeking behavior changes during pregnancy.